PENGARUH AERASI PADA FERMENTASI PADAT TANDAN KOSONG KELAPA SAWIT OLEH Aspergillus niger TERHADAP PRODUKSI GULA SEDERHANA - Himmatun Wisda, Wahyudi Budi Sediawan, Sarto (Jurnal Teknik Kimia USU, 2016)
The effects of aeration on production of simple sugars by Aspergillus niger were investigated using oil palm empty fruit bunch (OPEFB) by solid state fermentation using Aspergillus niger. Simple sugars can further be  fermented to produce bioethanol. OPEFB is renewable cellulosic biomass and largely available in Indonesia. Before being fermented, OPEFB needs to be pretreated. It was done by NaOH 1% solution at 150 ºC for 2 hours. The concentrations simple sugars produced by hydrolysis were analyzed by Dinitrosalicylic acid (DNS). It turned out that the highest concentration of sugars was to be 9,102 g/L, and it was obtained on the 3rd day of fermentation. Some parts of the sugars produced were consumed by Aspergillus niger itself for growth and maintenance. The experiment showed that aeration increased the simple sugars concentration. Modelling of reaction kinetic assumed to hydrolisis process and simple sugar consumed. Simply modelling can describe in quantitative fermentation of OPEFB. Moreover, get parameters value at equation of reaction kinetic.